A survey about the attitude of peoples about consumption of fast foods, Yazd, Iran - Baghianimoghadam, Mohammad Hosein; Fazelpour, Shokouh; Nadgarzadah, Azadeh; Falahzadah, Hosein; Baghianimoghadam, Behnam (Progress in Nutrition, 2014)
Introduction: The use of high calorie food and fat such as fast foods and imbalance between energy intakes increases the risk of obesity, hypertension, cardiovascular diseases, diabetes type two and other diseases. Obesity and its’ complications is one of the most public health problems worldwide. The aim of this study is to determine the attitude of people of Yazd city about consumption of fast foods. Materials and Methods: This was a cross- sectional descriptive study. Totally 600 residents of Yazd city were over 18 years selected by cluster sampling among different distinct of the city. The data was collected by a researcher made questionnaire which its validity and reliability was approved by a team of experts and pilot testing. Data was gathered by the researcher interview during home visits. After completion of questionnaires, all gathered data were transferred into SPSS-15 software and analyzed. Results: From all 600 participants 66% were women and 34% were men. The data of the study showed that the attitude of men on using the fast food is more positive than women and there is significant difference between their attitude (P